Depredación por larva de escarabajo de agua (Coleoptera: Dytiscidae) y canibalismo en Lithobates berlandieri (Anura: Ranidae) en Huatusco, Veracruz, México - Vásquez-Cruz, Víctor; Reynoso-Martínez, Arleth (Instituto de Ecología, A.C., 2018)
We documented for the first time, a depredatory event along with cannibalism, where two tadpoles of Lithobates berlandieri approached to the body of a tadpole while being predated by the larva of dytiscid and fed on it. This case of cannibalism suggest a competitive response.